Вы находитесь на странице: 1из 16

1

... 23.09.04.

: |

1:
.

.
( )
- .
- , .
, .
( )

: . 1.1. . . .
. 1.2. . .
. 1.3. . Z-. . 1.4. . . . .
1.5. . . .
. . . . 1.6. . . .
. . . .
.

()
.
(, ),
( ) .
, , , , () ().
, ( , ) . ,
,
.
, , ( - ) .
,
. , - , -
,
.
1.1. /2,24/.
.

( ), TL:
y(kt) = TL{x(kt)}.
:
M

m=0

n= 0

am y(kt-mt) = bn x(kt-nt),

(1.1.1)

k = 0,1,2,..- , t - , am bn , , . a0 = 1,
(1.1.1), , -

2
t = 1, :
N

n= 0

m =1

y(k) = bn x(k-n) am y(k-m).

(1.1.2)

, , (), - (, ). am bn k,
, .. .
( ).
. am
(1.1.2) x(k) bn:
N

y(k) = bn x(k-n).
n= 0

(1.1.3)

(1.1.3) k
"" . (). n ""
. N+1 , ,
.. "" , .
. k<n, k<m (1.1.2),
x(-k), k = 1,2,..,N,
y(-k), k = 1,2,..,M. , (0), .. x(0) .
. "", ""
k,
(1.1.3) :
N

y(k) = bn x(k-n).
n = - N'

(1.1.4)

N' = N . , , .
.
, x(k) sk
(. . 1.1.1).
bn hn ( h
). yk y(k)
, h0
sk, hn . 1.1.1. .
sk-n
.
yk. - hk,
sk ( sk ) , ..

3
x(k) () bn
( ).
(1.1.3-1.1.4) :
y(k) = b(n) * x(k-n).
()
(
). , 1.
, , ,
. , . , :
yk = 0.2(xk-2+xk-1+xk+xk+1+xk+2).
,
:
2

yk = bn xk-n,
n= -2

bn = 0,2.

(1.1.5)

, () :
yk = (-3xk-2+12xk-1+17xk+12xk+1-3xk+2)/35.
(1.1.6)
: b0 = 17/35, b1 = b-1 = 12/35, b2 = b-2 = -3/35.
2

. : yk =

bn xk-n, bn = 0,2. - .

n= -2

(): xk = {0,0,0,0,0,0,10,10,10,10,}.
: yk = {0,0,0,0,2,4, 6, 8,10,10,10,10,}.
. 1.1.2(). ( ,
. 1.1.1, ).
: 1,
. , "" .
. ( . 1.1.2()).

. 1.1.2.

:
1. :
h(t) * [a(t)+b(t)] = h(t) * a(t)+h(t) * b(t).
2. :
h(t) * a(t) * b(t) = a(t) * b(t) * h(t).
3. :
[a(t) * b(t)] * h(t) = h(t) * a(t) * b(t).
y(t) s(t) h(t).

4
. ,


(1.1.2), (), ,
, . ,
. 1.1.3. .
am. ,
: bn, "" (
) am,
"" . . 1.1.3.
. : yk = boxk+a1yk-1, bo = a1 = 0.5, y-1 = 0.
: xk = {0,0,1,0,0,0,0,0,0,0,1,1,1,1,1....}
:
o = 0,5xo + 0,5y-1 = 0; y1 = 0,5x1 + 0,5yo =0; y2 = 0,5x2 + 0,5y1 = 0.5; y3 = 0,5x3 + 0,5y2 = 0.25;
y4 = 0,5x4 + 0,5y3 = 0.125; y5 = 0,5x5 + 0,5y4 = 0.0625; y6 = 0,5x6 + 0,5y5 = 0.03125; ..
: yk = {0, 0, 0.5, 0.25, 0.125, 0.0625, 0.03125, 0.015625,...}

. 1.1.4. .

, , ,
( , ), ,
bk ( ).
. : yk = boxk - a1yk-1, bo = 0.5, a1=1.1, y-1 = 0
: xk = {0, 10, 0, 0, 0,....}.
: yk = {0,0,5,-5.5,6.05,-6.655,7.321,-8.053,8.858,-9.744,10.718,-11.79, ..}
: 1 " ".

. 1.1.5. .

, , , - . :
yk = (xk+xk-1)/2 + yk-1,
(1.1.7)
.. : bo = b1 = 0.5, a1 = 1.

5
. : yk=(xk+xk-1)/2+yk-1, - .
: xk={0,0,2,2,4,0,0,0,4,4,4,0,0,0,5,0,0,0,....}
. : yk= {0,0,0,1,3,6,8,8,8,10,14,18,20,20,20,22.5,25,25,25...}

1.1.6. .
1.2. .
. ( -

), k = 0, , :
y(k) = TL[(0)] = bn * (0-n) = h(k) bn.
(1.2.1)
h(k),
, ( ).

x(k) = 0 x(k-n),
n =

, ,
:
y(k) = n h(n) (0 x(k-n)) n h(n) x(k-n).

h(n).
, ,
,
b(n), (1.2.1), : h(n)
b(n).
(1.1.2), k = 0 . (1.2.1)
.
. : yk = xk + 0.5yk-1.
: xk= o= {1,0,0,0,...}.
:
yo = xo+0.5 y-1 = 1+0 = 1 = ho. y1 = x1+0.5 yo = 0+0.5 = 0.5 = h1. y2 = x2+0.5 y1 = 0+0.25 = 0.25 = h2.
y3 = x3+0.5 y2 = 0.125 = h3.
y4 = x4+0.5 y3 = 0.0625 = h4, ..
: hk = (O.5)k, k = 0,1,2....


( ), uo(k) = 1 k
0, uo(k) = 0 k < 0:
N

n= 0

n= 0

g(k) = h(n) uo(k-n) = h(n).


:

h(k) = g(k) - g(k-1).


g(k) (
).
. 1.1.4 ( k = 10 )
k = 2.
1.3. /7/.
Z-. -

z-. z-
(1.1.1), c (y(k-m) zm Y(z)), :
M

m=0

n= 0

Y(z) amzm = X(z) bnzn,

(1.3.1)

X(z),Y(z)- z- . , ao
= 1, - z-:
N

n= 0

m =1

H(z) = Y(z)/X(z) = bnzn (1+ amzm).

(1.3.2)

:
N

H(z) = bnzn.

(1.3.3)

n= 0

, , H(), Z- H(z)
. :
Y(z) = H(z)X(z).
M

Y(z)(1+

amz ) = X(z) bnzn


m

m =1

Y(z) = X(z)

n=0

n=0

m =1

bnzn Y(z) amzm.

(1.3.4)

Z- (1.3.4):
y(k) =

n=0

m =1

bnx(k-n) amy(k-m).

(1.3.5)

, z-
(z) = zn = 1,
y(k) h(k), :

H(z) = Y(z)/(z) = Y(z) = TZ[y(k)] = h(k)zk,


k=0

(1.3.6)

.. z- . z- :
h(k) H(z).
(1.3.7)
H(z) ,
, z- z.
(1.3.2), , , .. , -

7
. -,
-.
-, .. .
.
1. : H(z) = (1-z5)/(1-z).
: H(z) = 1+z+z2+z3+z4.
H(z) h(n) = {1,1,1,1,1}. -.
2. : H(z) = 1/(1-2z).
z-: h(n) = 2n. -.
. , .
:
(1.3.8)
n |h(n)| < .
.
H(z) z-, |z| 1, , , ()
z-. H(z) (1.3.2).

.
. 1.1.4: H(z) = b0/(1-a1z). 1= 0.5 : z=
2. |z|>1. .
. 1.1.5: H(z) = b0/(1+a1z). 1= 1.1 : z= 0.909. |z| < 1. , .
. 1.1.6: H(z) = 0.5(1+z)/(1-z). : z= 1.
, , k = .
h(n) = {0.5,1,1,1, .}, n = , .. .
.

, ..
.

( ), .
1.4.
.

/2,13,24/.

z- z =

exp(-jt) (1.3.2) - , ..
, .

.
, , x(kt) =
B() exp(jkt), y(kt) = A() exp(jkt).
(1.1.1), :
M

m=0

n= 0

am A() exp(jkt-jmt) = bn B() exp(jkt-jnt).

A() exp(jkt)

m=0

n= 0

am exp(-jmt) = B() exp(jkt) bn exp(-jnt).

8
A()

m=0

n= 0

am exp(-jmt) = B() bn exp(-jnt).

(1.4.1)

( =1):
H() = A()/B() =

n= 0

m =1

bn exp(-jnt) [1+ am exp(-jmt)].

(1.4.2)

,
(1.3.2) z = exp(-jt), . z- (1.3.7),
- ,
. t = 1:
H() =

h(n) exp(-jn),

n =

(1.4.3)

h(n) = (1/2) H() exp(jn) d.


-

(1.4.4)

H() , R() - (), () - ().


A() = |H()| = Re 2 H ( ) + Im 2 H ( )

() = arctg(-Im H()/Re H()).


. 1.4.1-1.4.3 ( ), . 1.1.4
1.1.6. z=exp(-jt) t=1 H(z).

. 1.4.1. .

. 1.4.2. .

. 1.4.3. . .
.
:

1. .
2. t H() -

9
. H() F = 1/t.
( -/t /t, f -1/2t 1/2t)
. N, N = /t. .
3. h(nt)
, - . 0-N .
.
, t
1, (0,) (0,1/2) f.
() 0 2 ( 0 1 ), ( - 0) 2 (
). ,
,
2, 0, . 0 N N+1 - , 2/(N+1). ,
N (N+1)/2, , N ( k=N/2 N/2 +1). k (
k=0) N+1-k (
k=(N+1)/2 N).
. , , , .
, . sin t, , , sin(t-), :
sin(t-) = sin (t-tp),
t- = (t-tp).
, tp :
(1.4.5')
tp = /.
(1.4.5) :
tp()= () /.
(1.4.5)
tp()
,
, .. ,
.
, , , .
, , ,
tp , ().

10
,
:
s(t) = cos 1t + cos 2t.
:
s(t) = 2 cos[0.5(1+2)t] cos[0.5(1-2)t].
, 1 2 , (1+2)/2
(1-2)/2. 1 2 , , :
s(t) = cos (1t-1) + cos(2t-2).
:
s(t) = 2 cos[0.5((1+2)t-(1+2))] cos[0.5((1-2)t-(1-2))].
tg:
cos[0.5((1-2)t-(1-2))] = cos[0.5(1-2)(t-tg)].
:
(1-2)tg = 1-2.
(1.4.6)
tg = (1-2)/(1-2) = /.

:
tg()= d()/d.
(1.4.7)

:
Ln(H()) = ln |H()| + j(),
() = Im[Ln(H()].
tg()= d /d = Im{d[Ln(H())]/d} = Im{dH()/[H()d]}. (1.4.8)
:
tg(k) (2/)Im{(Hk+1-Hk) / (Hk+1+Hk }.
(1.4.9)
1.5. /4,15,24/.

,
. - ,
, , .
.
, ,
x(kt) ,
y(kt) . t, , 1.
, h(n) = exp(-an), n 0.
, , :
x(k) = A + cos(2k+),
A - , [0, 2]. :
y(k) = h(n) * x(k-n)

h(n)x(k-n) = A/3 + [3cos(2k+) + 2sin(2k+)]/13.

n=0

,
, , , ,
.
-

11
x(k) :
y = {y(k)}= M{ n h(n)x(k-n)}= n M{x(k-n)}h(n) =

= x n h(n) = x .
(1.6.1)
, , . = 1 .
( ),
.
. x(k)
(0-) () :
K -n

Rx(n) = [1/(K+1-n)]

x(k)x(k+n).

n=0

. y(k) y(k+n), , :
y(k)y(k+n) = j i h(i)h(j) x(k-i)x(k+n-j).
, ,

M{x(k-i) x(k+n-j)} = -Rx(k-i-k-n+j) = Rx(n+i-j),
:
Ry(n) = i j h(i)h(j) Rx(n+i-j) Rx(n) * h(n+i) * h(n-j).
(1.6.2)
, , , , , . . . 1.5.1
RC, .

. 1.5.1. .

, , nj = m,
:
h(n+i) * h(n-j) = h(m+i+j) * h(m) = h(m) * h(m+p) = Kh(m),
Kh(m) - . :
(1.5.2')
Ry(n) = Rx(n) * Kh(m).
, . k
, -

12
( 0.5):
= / =1/2f.
() , , R(n):
k = 2n|R(n)/R(0)| - 1,
n 3-5 0.1R(0) (
R(n) , ).
, , k
.
Rx(n)
-,
Kh(m) ,
Kh(m).
Ry(n) , .
1.5.2, . 1.5.1 . 1.5.2.
=10000. , .


:
k = 2n|Kh(n)/Kh(0)| - 1, n 0.
() Rxy
:
x(k)*y(k+n) = i h(i) x(k)y(k+n-i) .
Rxy(n) = i h(i) Rx(n-i) h(i) * Rx(n-i).

(1.6.3)

.. .
.
Ryx :
(1.5.3')
Ryx(n) = Rxy(-n) h(i) * Rx(n+i).
,
(h(i) = 0 i<0) Rxy(n)
0 n<0, Ryx 0 n>0.
.
h(k) H(f) x(k) X(f),
Rx(n) Wx(f),
y(k) YT(f) = X(f)H(f). , :
2
2
2
|YT(f)| = |XT(f)| |H(f)| .
(1.5.4)
( ):
2
2
2
Wy(f) (1/T) |X(f)| |H(f)| = Wx(f) |H(f)| .
(1.5.5)
, . -

13

.

:
Ry(n) |Y()|2 = Wy().
( )
(1.5.5):

y = Ry(0) = Wx(f) |H(f)|2 df Rx(0) n h2(n) = x2 n h2(n).


2

(1.5.6)

,

:

y = y (t) = Ry(0) x
2

n h (n)
2

Wx(f) |H(f)|2 df,

(1.5.7)

: , .
. :

y2 = y2 - y ( x2 - x ) n h2(n).
(1.5.8)
:
2
Wxy(f) (1/T)XT(f)YT(f) = (1/T)|XT(f)| H(f) = Wx(f)H(f).
(1.5.9)
, :
Rxy(n) = Rx(n) * h(n),
(1.5.10)
(1.5.3).
.

( ). (k)
M{(k)}= 0 2. (k) . :
2

y(k) = n h(n)[x(k-n)+(k-n)].
:
M{y(k)}= n h(n)[x(k-n)+M{(k-n)]}= n h(n)x(k-n).
:
D{y(k)}= M{[n h(n)[x(k-n)+(k-n)]-M{y(k)}]2}=

= M{[n h(n) (k-n)]2}= n h2(n) M{2(k-n)}= 2 n h2(n). (1.5.11)


,
,
, . (1.5.7) Wx(f) = 2:

y = |H(f)|2 df 2 n h2(n).
2

(1.5.11')

, :
2
(1.5.12)
Kq = n h (n).
:
Kq = [1/(N+1)] n Hn2.

(1.5.12')

14
2

. : y(k) = 0.2

k = 2

x(k-n).

: 5 (0,22) = 0,2. 1/0.2 = 5 .


.
: 0.486.
-

xy2(f) = |Wxy(f)|2/[Wx(f)Wy(f)].
(1.5.12)
Wx(f) Wy(f) -,
f :
0 xy2(f) 1.
- ( ) .
1, , (1.5.12) Wxy Wy, Wx.
.
0 1 :
1. ( ) (, ).
2. . , , ,
..
3. y(t) x(t) -
.
1-xy2(f) y(t) f, x(t).

/4/.
1.6. /8,21/.

( )
, 1.6.1
.
,
,

. 1.6.1. .
, .

15

,
.
H(z) = (1+b1z)/(1+a1z) ,
, 1.6.2. i - xi(k)
Xi(z),
z- .
ij - ( i j)
. 1.6.2. .
,
.
. .
1. (. 1.6.3). . 1.6.3.
. , : H(z) = H1(z)H2(z)...HN(z).
2. (. 1.6.4).
, .
. 1.6.4.
, : H(z) = H1(z)+H2(z)+...+HN(z).
3. (. 1.6.5).

, ,
(
. 1.6.5.
), . : H(z) = H1(z)/(1H1(z)H2(z)).
. :
1. (. 1.6.6)
yk =

n= 0

m =1

bnxk-n amyk-m,


H(z) =

n= 0

m =1

bnzn /(1+ amzm).

. 1.6.6.

2.
.
:
H(z) = Y(z)/X(z) = H1(z)H2(z),
M

H1(z) = V(z)/X(z) = 1/(1+

amzm),

m =1

H2(z) = Y(z)/V(z) =

bnzn.

n= 0

16
M

: v(k) = x(k) -

amv(k-m),

m =1

(1.6.1)

y(k) =

bnv(k-n).

n= 0

(1.6.2)
(1.6.1-1.6.2)
v(k).
. 1.6.7.
1.6.7.
3. ()
:
k

H(z) = Hi(z).
i =1

Hi(z) - (1-riz)/(1-piz) H(z) , ri pi - H(z). Hi(z)


- :
Hi(z) = (b0i + b1i z + b2i z2) / (1 + a1i z + a2i z2).
4. .
.
.
- () , , .
.

. 1.6.8.
(
) . 1.6.8.

2. .. : . - .: , 1988.- 448 .
4. ., . . .: , 1989.
540 .
7. .. . : . - .:
, 1985.- 312 .
8. .. . : . - .: , 1990.- 256 .
13. ..
. .: , 1981. 304 .
15. ., . .
.: , 1989. 376 .
21. ., . . .:
, 1978. 848 .
24. .. . .: , 1987. 221 .

Оценить